External debt management - Mehran, Hassanali; IMF Institute; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1985)
This book contains proceedings of a seminar which was designed to provide a forum for national officials, international bankers, and staff members of the Fund and the World Bank to exchange views and discuss issues and practices arising out of their experience with external debt matters. The focus of the seminar was on External debt, emphasis was laid on the implications to policy makers, and for the Fund's role in the adjustment of the process.
"Papers presented at a seminar organized by the IMF Institute and the Central Banking Department of the International Monetary Fund, held in Washington in December 1984."
usc 16/08/2018
Loans
Keywords: Debts, External; Loans, Foreign